Biotechnological Production of Polyhydroxyalkanoates: A Review on Trends and Latest Developments. (24th February 2014) - Singh Saharan, Baljeet; Grewal, Anita; Kumar, Pardeep
Abstract : Polyhydroxyalkanoates (PHA) producers have been reported to reside at various ecological niches which are naturally or accidently exposed to high organic matter or growth limited conditions such as dairy wastes, hydrocarbon contaminated sites, pulp and paper mill wastes, agricultural wastes, activated sludges of treatment plants, rhizosphere, and industrial effluents. Few among them also produce extracellular by-products like rhamnolipids, extracellular polymeric substances, and biohydrogen gas. These sorts of microbes are industrially important candidates for the reason that they can use waste materials of different origin as substrate with simultaneous production of valuable bioproducts including PHA. Implementation of integrated system to separate their by-products (intracellular and extracellular) can be economical in regard to production. In this review, we have discussed various microorganisms dwelling at different environmental conditions which stimulate them to accumulate carbon as polyhydroxyalkanoates granules and factors influencing its production and composition. A brief aspect on metabolites which are produced concomitantly with PHA has also been discussed. In conclusion, exploring of capabilities like of dual production by microbes and use of wastes as renewable substrate under optimized cultural conditions either in batch or continuous process can cause deduction in present cost of bioplastic production from stored PHA granules.